Fetal Body Composition and Organ Growth in Pregnancies Complicated by First-Trimester Vaginal Bleeding Status: NICHD Fetal 3D Study - Jean-Louis, Alexandra; Gleason, Jessica L.; Chen, Zhen; Wagner, Kathryn A.; He, Dian; Newman, Roger; Grobman, William A.; Gore-Langton, Robert; Sherman, Seth; Cortes, Magdalena Sanz; Chien, Edward K.; Goncalves, Luis F.; Grewal, Jagteshwar; Grantz, Katherine L. (American Journal of Perinatology, 2025)
This study aimed to explore associations between self-reported first-trimester vaginal bleeding status and fetal body composition and organ volumes measured by three-dimensional (3D) ultrasound across pregnancy.The NICHD Fetal 3D Study (2015–2019) included individuals with singleton pregnancies at low risk for fetal growth abnormalities (n = 2,634). Fetal body composition measures of arm, abdomen, and thigh, and organ volumes including cerebellum, lung, kidney, and liver, were measured up to five times between 15 and 40 weeks using 3D ultrasound. Women were grouped by cumulative days of self-reported first-trimester vaginal bleeding: 0 (no bleeding, reference), 1, or >1 day. Linear mixed models, with quadratic and cubic terms for gestational age, including global tests for overall differences in trajectories and weekly pairwise comparisons, were fit to compare groups by fetal anthropometric measures, adjusted for maternal age, race/ethnicity, prepregnancy body mass index, parity, and infant sex.Most women had no bleeding (n = 2,144, 81.4%), whereas 211 (8.0%) reported 1 day and 279 (10.6%) reported >1 day. Compared with no bleeding, fetuses of women with >1 day of bleeding had 75.1 to 264.0 mm2 smaller abdominal area between 30 and 40 weeks, 1.1 to 4.0 cm3 smaller fractional thigh volume between 33 and 40 weeks, 0.4 to 2.4 cm3 smaller fractional fat thigh volumes between 30 and 40 weeks, and 0.8 to 1.6 cm3 larger cerebellar volumes between 35 and 40 weeks. Fetuses of women with 1 day of bleeding had 2.6 to 4.8 cm3 smaller liver volume between 26 and 35 weeks compared with no bleeding.First-trimester bleeding was associated with smaller fetal abdominal area and decreased adiposity compared with no bleeding, whereas organ growth trajectories were increased for the cerebellum and decreased for the liver. Fetal 3D measures may provide insight into how first-trimester gestational bleeding potentially influences fetal growth and development with implications for possible postnatal health outcomes.
Keywords: first-trimester bleeding; fetal growth; body composition; organ growth; fetal development